2017
DOI: 10.1002/hbm.23486
|View full text |Cite
|
Sign up to set email alerts
|

Addressing reverse inference in psychiatric neuroimaging: Meta‐analyses of task‐related brain activation in common mental disorders

Abstract: Functional magnetic resonance imaging (fMRI) studies in psychiatry use various tasks to identify case‐control differences in the patterns of task‐related brain activation. Differently activated regions are often ascribed disorder‐specific functions in an attempt to link disease expression and brain function. We undertook a systematic meta‐analysis of data from task‐fMRI studies to examine the effect of diagnosis and study design on the spatial distribution and direction of case‐control differences on brain act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(94 citation statements)
references
References 56 publications
5
88
0
1
Order By: Relevance
“…In line with these data a recent study by our research group demonstrated that SCZD, OCSD and ASD do not show distinctive patterns of GM alterations; rather, these three spectra showed a common pattern, which can be divided into two clusters of alterations extending across the insulae, medial thalamic and the cingulate cortices (Cauda, et al, 2017). This finding was also recently supported by a study on functional alterations (Sprooten, et al, 2017), which has showed that very few functional differences can be statistically observed in a variety of psychiatric conditions (i.e., schizophrenia, bipolar disorder, major depressive disorder, anxiety disorders, and obsessive compulsive disorder). Of note, this specific pattern of alterations common to SCZD, OCSD, and ASD is probably not only shared by these three spectra, but also by other psychiatric disorders (Buckholtz & Meyer-Lindenberg, 2012;Caspi, et al, 2014;Crossley, et al, 2014;McTeague, et al, 2016).…”
supporting
confidence: 84%
“…In line with these data a recent study by our research group demonstrated that SCZD, OCSD and ASD do not show distinctive patterns of GM alterations; rather, these three spectra showed a common pattern, which can be divided into two clusters of alterations extending across the insulae, medial thalamic and the cingulate cortices (Cauda, et al, 2017). This finding was also recently supported by a study on functional alterations (Sprooten, et al, 2017), which has showed that very few functional differences can be statistically observed in a variety of psychiatric conditions (i.e., schizophrenia, bipolar disorder, major depressive disorder, anxiety disorders, and obsessive compulsive disorder). Of note, this specific pattern of alterations common to SCZD, OCSD, and ASD is probably not only shared by these three spectra, but also by other psychiatric disorders (Buckholtz & Meyer-Lindenberg, 2012;Caspi, et al, 2014;Crossley, et al, 2014;McTeague, et al, 2016).…”
supporting
confidence: 84%
“…Basic motor control and behavior are linked with a rich set of cortical and sub-cortical brain regions (10), an aspect that is appropriately recognized in the Research Domain Criteria constructs matrix (129). Whether the explication of domain related effects will ultimately inform and transform the diagnostic concept of schizophrenia, is itself an open question (130, 131), yet one worthy of investigation.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Given the critical role of the amygdala in anxiety and consistently observed hyperresponsivity in this region in anxiety-related disorders [18, 36, 37], previous rt-fMRI NF studies trained subjects to downregulate neural activity in this region and demonstrated that this strategy has the potential to enhance ER and attenuate anxious arousal [38-41]. In line with current neurocircuitry models of ER, successful downregulation of the amygdala was accompanied by increased functional connectivity between the amygdala and prefrontal regulatory regions in both, healthy subjects [39, 42] as well as patient populations with exaggerated anxiety [40, 43].…”
Section: Introductionmentioning
confidence: 99%